Role of School Administration in Providing an Attractive and Safe School Environment to Students under Vision 2030 - Obied Qaralleh, Thikryat Jibril (2020)
This study aimed to identify the role of school administration in providing an attractive and safe school environment for students as one of the requirements to achieve Vision 2030 in public schools in Al-Kharj. A random sample of (16%) of the study population was selected. The questionnaire was distributed to all the study sample. The study has reached several results including: the average response was much higher when asked about the role of school administration in providing an attractive and safe school environment for students. Statistically significant differences between the mean values were observed from the samples towards educational stage in favor of the primary and secondary levels. The results also showed that there were statistically significant differences between the mean values of the respondents according to the gender variable in the tool as a whole in favor of females. The researcher suggested several recommendations such as improving the level of students to be creative individuals in their community, encouraging educational initiatives that contribute to creating an attractive and safe school environment, and encouraging local community institutions to make donations to the schools and involve them in developing the students psychological, cognitive and physical health.